2007
DOI: 10.1038/sj.jes.7500575
|View full text |Cite
|
Sign up to set email alerts
|

Exposure modeling of high-frequency electromagnetic fields

Abstract: We developed a geospatial model that calculates ambient high-frequency electromagnetic field (HF-EMF) strengths of stationary transmission installations such as mobile phone base stations and broadcast transmitters with high spatial resolution in the order of 1 m. The model considers the location and transmission patterns of the transmitters, the three-dimensional topography, and shielding effects by buildings. The aim of the present study was to assess the suitability of the model for exposure monitoring and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 9 publications
2
49
0
Order By: Relevance
“…The far-field component aggregates the exposure from environmental sources. To predict the exposures from radio and television broadcast transmitters and mobile phone base stations a geospatial propagation model was used (Bürgi et al 2010;Bürgi et al 2008).…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%
“…The far-field component aggregates the exposure from environmental sources. To predict the exposures from radio and television broadcast transmitters and mobile phone base stations a geospatial propagation model was used (Bürgi et al 2010;Bürgi et al 2008).…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%
“…over several years, or on past exposure. Previous epidemiological studies have utilized other exposure assessment methods to estimate RF-EMF exposure which include spot measurements in bedrooms (Berg-Beckhoff et al, 2009;Hutter et al, 2006;Tomitsch et al, 2009), self-reported (Navarro et al, 2003;Santini et al, 2003) or geo-coded distance of the residence to the closest mobile phone base station , and geospatial modeling of broadcast transmitters or mobile phone base stations (Bürgi et al, 2010;Bürgi et al, 2008;Ha et al, 2007;Neitzke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We used a three-dimensional geospatial propagation model for the study area in which RF-EMF from fixed site transmitters (frequency bands are shown in Table 1) was modeled (in-and outside of buildings) (Bürgi et al, 2010;Bürgi et al, 2008). The model calculation was based on a comprehensive database of all transmitters (position, transmission direction, antenna types and radiation pattern, transmitter power and number of channels) and a threedimensional building model of the study area, considering shielding and diffraction by buildings and topography.…”
Section: Geospatial Propagation Modelmentioning
confidence: 99%
“…For mobile phone calls we also considered the type of network that was used for each call, either directly obtained from the operator data or estimated for selfreported data by mixed linear regression models with school as cluster variable calibrated on the operator data using the following predictors: type of mobile phone operator, use of mobile internet on mobile phone (yes/no) and modelled UMTS exposure levels at home. The far-field component aggregates the exposure from environmental sources, which were derived from propagation modelling for radio and TV broadcast transmitters as well as for mobile phone base stations (Bürgi et al 2010;Bürgi et al 2008). Exposure from cordless phone base stations, WLAN access points and other people's mobile phones were estimated by linear regression models calibrated on the personal measurement data available from 95 study participants .…”
Section: Rf-emf Dose Measuresmentioning
confidence: 99%